Sequence polymorphism in the ribosomal DNA internal transcribed spacers differs among Theileria species - Aktas, Munir; Bendele, Kylie G.; Altay, Kuersat; Dumanli, Nazir; Tsuji, Masayoshi; Holman, Patricia J. (Elsevier, 2007)
The genomic region spanning the two ribosomal RNA internal transcribed spacers (ITS] and ITS2) and the 5.8S rRNA gene was cloned and sequenced from sixteen Theileria isolates. Each Theileria species possessed ITS] and ITS2 of unique size(s) and species specific nucleotide sequences. Varying degrees of ITS1 and ITS2 intra- and inter-species sequence polymorphism were found among, ruminant Theileria species. The spacers were most polymorphic in the agent of tropical theileriosis, Theileria annulata, and were more conserved in two benign species, Theileria buffeli and Theileria sergenti Chitose. Phylogenetic analysis of the rDNA ITS1-5.8S rRNA gene-ITS2 region clearly separated each taxon, placing them in three clusters. One held T annulata, Theileria parva, and Theileria mutans. with the latter two most closely related. The second held T sergenti Ikeda, T sergenti Chitose, and T buffeli. with the latter two most closely related. The third cluster held the Theileria ovis isolates. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: ribosonial RNA intergenic spacer; internal transcribed spacer; 5.8S rRNA gene; Theileria species; phylogenetic tree; polymorphism